Injury epidemiology after the 2001 Gujarat earthquake in India: a retrospective analysis of injuries treated at a rural hospital in the Kutch district immediately after the disaster - Phalkey, Revati; Reinhardt, Jan D.; Marx, Michael (Global health action, 2011)
BACKGROUND: The number of injured far exceeds those dead and the average injury to mortality ratio in earthquakes stands at 3:1. Immediate effective medical response significantly influences injury outcomes and thus the overall health impact of earthquakes. Inadequate or mismanagement of injuries may lead to disabilities. The lack of precise data from immediate aftermath is seen as a remarkable weak point in disaster epidemiology and warrants evidence generation. - OBJECTIVE: To analyze the epidemiology of injuries and the treatment imparted at a secondary rural hospital in the Kutch district, Gujarat, India following the January 26, 2001 earthquake. - DESIGN/METHODS: Discharge reports of patients admitted to the hospital over 10 weeks were analyzed retrospectively for earthquake-related injuries. - RESULTS: Orthopedic injuries, (particularly fractures of the lower limbs) were predominant and serious injuries like head, chest, abdominal, and crush syndrome were minimal. Wound infections were reported in almost 20% of the admitted cases. Surgical procedures were more common than conservative treatment. The most frequently performed surgical procedures were open reduction with internal fixation and cleaning and debridement of contaminated wounds. Four secondary deaths and 102 transfers to tertiary care due to complications were reported. - CONCLUSION: The injury epidemiology reported in this study is in general agreement with most other studies reporting injury epidemiology except higher incidence of distal orthopedic injuries particularly to the lower extremities. We also found that young males were more prone to sustaining injuries. These results warrant further research. Inconsistent data reporting procedures against the backdrop of inherent disaster data incompleteness calls for urgent standardization of reporting earthquake injuries for evidence-based response policy planning.